Do Interviewers Moderate the Effect of Monetary Incentives on Response Rates in Household Interview Surveys?. (11th January 2019) - Kibuchi, Eliud; Sturgis, Patrick; Durrant, Gabriele B; Maslovskaya, Olga
Abstract: As citizens around the world become ever more reluctant to respond to survey interview requests, incentives are playing an increasingly important role in maintaining response rates. In face-to-face surveys, interviewers are the key conduit of information about the existence and level of any incentive offered and, therefore, potentially moderate the effectiveness with which an incentive translates nonproductive addresses into interviews. Yet, while the existing literature on the effects of incentives on response rates is substantial, little is currently known about the role of interviewers in determining whether or not incentives are effective. In this article, we apply multilevel models to three different face-to-face interview surveys from the United Kingdom, which vary in their sample designs and incentive levels, to assess whether some interviewers are more successful than others in using incentives to leverage cooperation. Additionally, we link the response outcome data to measures of interviewer characteristics to investigate whether interviewer variability on this dimension is systematically related to level of experience and demographic characteristics. Our results show significant and substantial variability between interviewers in the effectiveness of monetary incentives on the probability of cooperation across all three surveys. However, none of the interviewer characteristics considered are significantly associated with more or less successful interviewers.